Mewujudkan Gereja yang Hidup melalui Implementasi Pastoral Berbasis Data - Cristofer, Derry; Palinoan, Frans Fandy; Tandiangga, Patrio (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
The church, which consists of God's people who are constantly changing, needs an effective pastoral ministry. In order for pastoral actors to carry out pastoral ministry effectively, pastoral actors must understand and recognize the condition of the people they serve. Thus, pastoral actors can carry out pastoral service planning that can truly answer the longings and needs of the people. In simple terms, the pastoral ministry like this is called data-based pastoral ministry or pastoral ministry with an empirical approach. In this paper, the researcher tries to provide basic ideas for conducting data-based pastoral ministry and provides a complete understanding of the importance of pastoral ministry through an empirical approach.